Exploring the Fitness Centre Industry in Malaysia; What Factors Influence Joining and Retention and Prevents People from Joining - Smith, Helen B (2008)
Malaysia’s fitness centre industry has seen rapid growth over the last 6 years with the opening of more than 25 international chain outlets of which the majority is owned by California Fitness, Celebrity Fitness, Fitness First and True Fitness. An increasing population and year on year GDP growth, together with the support of the Malaysian government, contribute to further the growth of the industry. The purpose of the study is to explore, investigate and reveal information about the growth and presence of Malaysia’s fitness centre industry as well as examine the reasons that affect people in their decision to join, remain, leave and, indeed, not join, a fitness centre. The research method was partially a qualitative approach and mainly quantitative via a self-administered electronic questionnaire. Data was collected via a web link and targeted at people predominately working and living in the Klang Valley. Findings showed that location featured as the primary reason for people leaving and the most important feature when choosing a fitness centre. However, as the analysis developed it became apparent there was indication of an overall lack of customer orientation in the fitness industry revealing the need for more effective staff – member, and social interaction. The study provides some insights into the features that influence people in their selection of a fitness centre; however, limitations have to be considered in the interpretation of the results. These limitations could be reduced with further thorough research.